THE FACTORS RELATED TO MOTHERS MOTIVATIONS IN CARRYING OUT THE CIRCUMCISION OF THE FEMALE CHILDREN IN ATEUK JAWO VILLAGE, BAITURRAHMAN SUB-DISTRICT, BANDA ACEH IN 2014 - Rahmayani, Rahmayani; Yunita, Ayuwari; Marniati, Marniati (Universitas Ubudiyah Indonesia, 2015)
The objective of this research is to detect the factors that affect the mothersâ motivations in carrying out the circumcision to female children in Ateuk Jawo Village, Baiturrahman Sub-District, Banda Aceh. The methodology used in this research is analytical descriptive with 121 population of people. The samples in this research are 55 people. The sampling technique is purposive sampling. The data was collected by distributing the questionnaires. This research was conducted in Ateuk Jawa Village, Baiturrahman Sub-Village, Banda Aceh on July 2014.The results of this research mention that Chi âSquare tests show that from 28 respondents who chose the culture were not affected to the low motivations of the mothers in carrying the circumcision, there were 16 respondents (57.1%) with the value of p = 0.003 (p <0.05). From the 32 respondents who chose the family supports were higher affected of the mothersâ motivations, there were 26 respondentsÂ Â (81.2%)Â Â with the value ofÂ pÂ =Â 0.004 (p < 0.05). The last was from the 25 respondents who chose the religion factor were the most affected of the mothersâ motivations, there are 21 respondents (84%), with the value of p = 0.010 (p <0.05).Keywords: Culture, Family Supports, Religion, Mothersâ motivations